Cardiovascular health through young adulthood and cognitive functioning in midlife. Issue 2 (26th February 2013) - Reis, Jared P.; Loria, Catherine M.; Launer, Lenore J.; Sidney, Stephen; Liu, Kiang; Jacobs, David R.; Zhu, Na; Lloyd‐Jones, Donald M.; He, Ka; Yaffe, Kristine
<x xml:space="preserve">Abstract</x> Objective A study was undertaken to examine the association between overall cardiovascular health as recently defined by the American Heart Association in young adulthood to middle age and cognitive function in midlife. Overall ideal cardiovascular health incorporates 7 metrics, including the avoidance of overweight or obesity, a healthful diet, nonsmoking, and physical activity, total cholesterol, blood pressure, and fasting glucose at goal levels. Methods This analysis of the Coronary Artery Risk Development in Young Adults study, a multicenter community‐based study with 25 years of follow‐up, included 2, 932 participants aged 18 to 30 years at baseline (year 0) who attended follow‐up examinations at years 7 and 25. Cardiovascular health metrics were measured at each examination. The Digit Symbol Substitution Test (DSST), modified Stroop test, and Rey Auditory Verbal Learning Test (RAVLT) were completed at year 25. Results A greater number of ideal cardiovascular metrics in young adulthood and middle age were independently associated with better cognitive function in midlife (p for trend < 0.01, for all). Specifically, each additional ideal metric was associated with 1.32 more symbols on the DSST (95% confidence interval [CI] = 0.93 – 1.71), a 0.77‐point lower interference score on the Stroop test (95% CI=−1.03 to −0.45), and 0.12 more words on the RAVLT (95% CI = 0.04 to 0.20). Participants who had ≥5 ideal metrics at a greater number of the 3 examinations over the 25‐year period exhibited better performance on each cognitive test in middle age (p for trend < 0.01, for all). Interpretation Ideal cardiovascular health in young adulthood and its maintenance to middle age is associated with better psychomotor speed, executive function, and verbal memory in midlife. ANN NEUROL 2013;73:170–179